Evaluation of the Blood Neutrophil-to-Lymphocyte Ratio (NLR) as a Diagnostic and Prognostic Biomarker in Dogs with Portosystemic Shunt - Anja Becher; Els Acke; Gonçalo Serrano; Ingmar Kiefer; Michaele Alef; Wolf von Bomhard; Romy M. Heilmann (Veterinary Sciences, 2024)
The neutrophil-to-lymphocyte ratio (NLR) can help in assessing inflammatory diseases, sepsis, and chronic hepatic conditions in humans. Dogs with congenital portosystemic shunts (PSSs) have signs of generalized inflammation, and the clinical signs can overlap with other conditions, including hypoadrenocorticism (HOC). Thus, the potential diagnostic and prognostic value of leukocyte ratios as surrogate markers was assessed in a retrospective case–control study including 106 dogs diagnosed with PSSs. The disease control groups were dogs with parenchymal hepatopathy (PH; n = 22) or HOC (n = 31). In the PSS dogs, the blood NLRs were associated with the severity of systemic inflammation but not with the shunt type, hepatoencephalopathy, systemic infection, or hypoglycemia. The baseline NLRs did not differ between the three disease groups, between medically and surgically treated PSS dogs, or between those with successful PSS ligation and dogs experiencing peri-/post-surgical complications. However, dogs requiring two consecutive surgical interventions had significantly higher NLRs, and an NLR of <2.53 distinguished dogs with successful shunt ligation in one surgery from those requiring two consecutive surgeries for PSS closure. The blood NLR might be a useful clinicopathologic variable in PSS, but its value in helping differentiate PSS from HOC cases appears low. Integrating the NLR into a diagnostic algorithm may allow for a prediction of the number of surgical interventions required.